The hospitalized preterm newborn: The significance of parents' participation in the Neonatal Unit - Josefina Gallegos-Martínez; Jaime Reyes-Hernández; Carmen Gracinda Silvan Scochi (Universidade de São Paulo, 2013)
OBJECTIVE: to identify and analyze the significance of participation for parents in a Neonatal Unit (NU) of a maternity hospital in San Luis Potosí, Mexico. METHOD: a qualitative study with 20 parents of both sexes, between 18 and 39 years of age, with a preterm hospitalized child. A content analysis using a thematic approach was used for information processing. RESULTS: the significance of: a) the NICU as a place of suffering and waiting, b) dealing with the child's admittance, c) being excluded from the hospitalized child's care and d) being aware of inadequacies in the child's care. CONCLUSION: parents deal with their suffering and experience barriers that impede their participation; they respond to the medical hierarchy that limits participation, even when it goes against their natural role as parents. The caregiving philosophy needs to be transformed so that parents are considered people with the right to participate and to be competent in caring for their child.